Enhancing Self-Management through Geragogy-Based Education in Older Adults with Uncontrolled Hypertension: A Randomized Controlled Trial - Ongkulna, Kiattisak; Pothiban, Linchong; Panuthai, Sirirat; Chintanawat, Rojanee; Chintanawat, Rojanee (Pacific Rim International Journal of Nursing Research, 2022)
Uncontrolled hypertension is a major medical problem leading to many serious health consequences. Enhancing self-management is essential for older adults with uncontrolled hypertension to control blood pressure and improve quality of life. Substantial evidence reveals that health literacy and self-efficacy are the strongest factors influencing self-management behaviors. According to geragogy, older adults require a different kind of education to other age groups. This randomized controlled trial investigated the effects of a Geragogy-Based Self-Management Education Program on health literacy, self-efficacy, and self-management behaviors among older adults with uncontrolled hypertension. One hundred participants who met the inclusion criteria were randomly assigned into experimental (n = 50) and control groups (n = 50). The experimental group received the self-management education program based on the geragogy teaching principle combined with transformative learning theory in addition to routine patient education, whereas the control group received only routine patient education. Data were collected at baseline, at the program end, and one and three months after the end of the program using the Health Literacy Scale, Hypertensive Self-Management Self-Efficacy Scale, and Self-Management Behaviors Scale. Data were analyzed using descriptive statistics, two-way repeated measures ANOVA, and independent sample t-test. The results demonstrated that after receiving the program, the experimental participants had significantly higher health literacy, self-efficacy, and self-management behaviors at all time-points of measurement than before commencing the program and the control participants. The findings of this study indicated a successful self-management education program. Further studies to ensure efficacy of this program are suggested.